The efficiency of corporate boards and firms’ audit fees - Nehme, Rabih (2018)
Purpose The quality of financial reporting for the financial institutions is vital for the public, as the negative consequences of manipulated financial statements will not only affect shareholders but also the regulators’ reputation and the society at large. The purpose of this paper is to assess the association between different corporate governance mechanisms and their impact on audit and reporting quality. The gender factor is introduced from a diverse boards’ perspective to highlight any impact of female presence on the quality of financial statements. Design/methodology/approach The authors examine a sample of financial institutions listed on the FTSE-350 index for the years 2011 to 2015. The financial sector has its own and different regulations, and financial reporting framework and auditors are expected to behave into more scrutiny. Bloomberg database is used to obtain governance and financial data, while firms’ annual reports are used to collect audit fees and audit committee information. A panel data regression is used to test hypotheses. The authors also control for unobservable heterogeneity, reverse causality and endogeneity. Findings The results suggest that boards with larger size and higher independence pay higher audit fees to enhance the monitoring capacity and protect the wider group of stakeholders. The results also show that women on boards are likely to reduce the risk of manipulated financial statements, as women are more inclined toward truthfulness, cautiousness and conservatism. In addition, the reported results show that audit committees with more independent members are more inclined toward obtaining higher quality audit to enhance firm’s reporting quality. Originality/value Given the recent governments’ intervention to avoid financial institutions’ negative impact on the economy, this study is relevant and provide policymakers insights into the existing relationships between audit fees and financial institutions’ governance structure.